Oral and otolaryngological complications of radiotherapy for head and neck cancers among patients attending Ocean Road Cancer Institute, Tanzania (Tanzania Medical Journal, 2019)
BackgroundThe prevalence of head and neck cancers is on the increase worldwide. Treatment modalities include surgery, radiotherapy and chemotherapy. The aim of this study was to determine the proportion of acute oral and otolaryngological complications of radiotherapy with or without chemotherapy for head and neck cancers.MethodsA retrospective cross-sectional, hospital based study was done to 80 patients with head and neck cancers who have just completed radiotherapy with or without chemotherapy at Ocean Road Cancer Institute (ORCI). Data was collected using a structured questionnaire within one week after completion of radiotherapy. Patients who reported hearing loss underwent otoscopy and audio-logical assessment including tympanometry and pure tone audiometry. Data was analyzed using SPSS program.ResultsThe proportion of males was higher than that of females in the ratio of 2:1 and majority of the patients involved were in the 6th decade of life, (27.5%). Out of the 80 study participants, 80% were found to have oropharyngeal mucositis, 90% were found to have xerostomia and 50% were found to have dysphagia. In addition, 76.2% of patients reported to have developed taste disorders after radiotherapy and 43.1% reported to have developed voice disorders. The proportion of hearing loss following radiotherapy was 21.9% though this should be taken with caution since there was no before and after intervention taken. Patients with sinonasal cancers had the least proportion of oral and oropharyngeal mucositis (50%), xerostomia (64.3%) and voice disorders (14.3%). Most of patients who developed hearing loss had nasopharyngeal cancer (85.6%) and salivary gland cancer (66.7%) while patients with oropharyngeal cancer, hypopharyngeal cancer and laryngeal cancer did not develop hearing loss at all.ConclusionOral and otolaryngological complications of radiotherapy with or without chemotherapy for head and neck cancers at ORCI are quite prevalent. Prevention of complications should be highly regarded especially by using shield protectors on uninvolved areas and advanced radiotherapy machines should be considered to minimize such complications.Key words: Oral, otolaryngological, head, neck, cancers, Tanzania.